2013
DOI: 10.1044/1059-0889(2013/11-0025)
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Occlusion and Comfort in Receiver-in-the-Ear Hearing Aids

Abstract: Self-perceived occlusion was greatest for power domes, although average level of occlusion did not exceed moderate occlusion on the rating scale. Perceived physical comfort was highest with the open dome and participants' own aids. Plus and power domes were respectively ranked as more uncomfortable than open domes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…18 20 Many studies in cochlear hearing loss have demonstrated the benefit with RIC over a BTE. 16 17 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 20 Many studies in cochlear hearing loss have demonstrated the benefit with RIC over a BTE. 16 17 …”
Section: Discussionmentioning
confidence: 99%
“…16 17 With the ear canal open, hearing aid users generally report a more natural and clear sound quality. 18 19 20 The larger distance between the receiver and microphone leads to less feedback and gives an opportunity to use open dome fitting, which reduces the chance of occlusion in the hearing aid users.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, although the "occlusion effect" attribute is deemed to be a significant discomfort attribute for earplugs wearers such as workers (Berger and Voix 2018;Casali et al 1987), musicians (Bernier 2013;Killion 2012;Laitinen and Poulsen 2008) or hearing aids wearers (Branda 2012;Conrad and Rout 2013;French-Saint George and Barr-Hamilton 1978;Furstenberg, Gordon, and Baccaro 1988;Killion, Wilber, and Gudmundsen 1988;Kochkin 2000;Mackenzie, Browning, and McClymont 1989), few HPD comfort studies incorporate questions about this effect in their questionnaires and it is therefore very difficult to estimate its contribution to overall comfort in general. Brown-Rothwell (1986) measures an item on the voice level (item: "I find it difficult to judge how loudly to speak to others") and relates it to the degree of occlusion experienced and thus to the possible occlusion effect.…”
Section: Acoustical Dimension Of Comfortmentioning
confidence: 99%
“…It is worth noting that the vast majority of studies on the relationship between comfort and perceived occlusion deal with hearing aids (Alworth et al 2010). The perceived occlusion is evaluated from perception tests of the quality of one's own voice (by reading sentences displayed on a screen aloud while wearing the hearing aid) or listening tests of external voices (Conrad and Rout 2013). Examples of attributes used to judge the quality of the voice are "boomy", "hollow", "resonant", "sounds like talking in a barrel".…”
Section: Acoustical Dimension Of Comfortmentioning
confidence: 99%
“…Another important specification shared by most of the IEDs is related to the quality of the acoustic seal at the ear canal/IED interface that should insulate adequately the eardrum from external noise. However, the usability and/or the efficiency of such devices can be limited by three major discomfort components also related to the quality of the mechanical and acoustic seals : (i) the physiological comfort component characterized by attributes such as friction, irritation or the mechanical pressure exerted by the device on the body, (ii) the acoustical comfort component characterized by attributes such as over-or under-attenuation of external noise, difficulty in communication, occlusion effect or acoustical feedback and (iii) the functional comfort component characterized by attributes such as the ease of insertion or the looseness of the fit (French-Saint, et al, 1978;Casali, et al, 1987;MacKenzie, et al, 1989;Park, et al, 1991;Harrison, 1993;Azeres, et al, 2008;Kochkin, 2000;Pirzanski, et al, 2004;Davis, 2008;Conrad, et al, 2013;Davis, et al, 2016;Doutres, et al, 2017).…”
Section: Introductionmentioning
confidence: 99%